Milton contractualiste : le thème du convenant dans The Tenure of Kings and Magistrates - Franck Lessay (Etudes Epistémè)
In The Tenure of Kings and Magistrates, John Milton articulated his own personal reading of the covenant, which firmly places him in the category of contractualist political thinkers. Though Milton’s contractualist thinking may be contemporary to Hobbes’s, it bears many more similarities to that of Locke, of whom Milton can somehow be seen as a forerunner.